Protective effects of conditioned media of immortalized stem cells from human exfoliated deciduous teeth on pressure ulcer formation - Katahira, Yasuhiro; Murakami, Fumihiro; Inoue, Shinya; Miyakawa, Satomi; Sakamoto, Eri; Furusaka, Yuma; Watanabe, Aruma; Sekine, Ami; Kuroda, Masahiko; Hasegawa, Hideaki; Mizoguchi, Izuru; Yoshimoto, Takayuki (Frontiers in Immunology, 2023)
Pressure ulcers (PUs) are increasing with aging worldwide, but there is no effective causal therapy. Although mesenchymal stem cells (MSCs) promote cutaneous wound healing, the effects of the conditioned medium (CM) of MSCs on cutaneous PU formation induced by ischemia-reperfusion injury have been poorly investigated. To address this issue, herein, we first established an immortalized stem cell line from human exfoliated deciduous teeth (SHED). This cell line was revealed to have superior characteristics in that it grows infinitely and vigorously, and stably and consistently secretes a variety of cytokines. Using the CM obtained from the immortalized SHED cell line, we investigated the therapeutic potential on a cutaneous ischemia-reperfusion mouse model for PU formation using two magnetic plates. This is the first study to show that CM from immortalized SHEDs exerts therapeutic effects on PU formation by promoting angiogenesis and oxidative stress resistance through vascular endothelial growth factor and hepatocyte growth factor. Thus, the CM of MSCs has potent therapeutic effects, whereas these therapies have not been implemented in human medicine. To try to meet the regulatory requirements for manufacturing and quality control as much as possible, it is necessary to produce CM that is consistently safe and effective. The immortalization of stem cells could be one of the breakthroughs to meet the regulatory requirements and consequently open up a novel avenue to create a novel type of cell-free regenerative medicine, although further investigation into the quality control is warranted.